Cr–Ag coatings: synthesis, microstructure and antimicrobial properties. (3rd July 2019) - Karami, Afshin; Zhang, Hu; Pederick, Victoria G.; McDevitt, Christopher A.; Kabir, Mohammad Sharear; Xu, Song; Munroe, Paul; Zhou, Zhifeng; Xie, Zonghan
ABSTRACT: Cr–Ag coatings for antimicrobial surface applications were fabricated by magnetron sputtering. The coating microstructure and mechanical properties were characterised using XPS, XRD, FESEM, TEM and nanoindentation measurement as a function of Ag content. The antimicrobial efficacy of these Cr–Ag coatings was evaluated against the pathogenic bacteria Escherichia coli and Staphylococcus aureus, revealing varied levels of bacterial killing. This study warrants further investigation into the antimicrobial mechanism of action of silver and future applications of Cr–Ag as antimicrobial coating for healthcare settings.